Specification for nickel-iron-chromium-molybdenum-aluminium-titanium heat-resisting alloy billets, bars, forgings and parts (Ni/Co 43.5, Cr 16.5, Mo 3.3, Al 1.2, Ti 1.2, Fe remainder). (29th August 1980) - British Standards Institution,
No abstract available